BIOMASS ANALYSIS OF COMMERCIALLY IMPORTANT EUGLENA GRACILIS CULTIVATED ON BBM, BG-11, AND CHU #10 GROWTH MEDIA - Syeda Amna Batool; Ghazala Yasmeen Butt (Journal of Animal and Plant Sciences, 2025)
Microalgae have been utilized as a potential biomass source for food and other products over the past few decades. Euglenagracilis is considered a promising candidate among commercially important microalgae. The commercialization of E.gracilis production is centered around the "5Fs of Biomass" approach, which includes the development and manufacturing of commercial products such as food, fiber, feed, fertilizer, and fuel derived from biomass. The chemical composition of culture media affects the yield of algae therefore; media optimization is important for the commercialization of microalgae-based products. This study aims to identify the most suitable culture medium for E. gracilis by evaluating biomass production to optimize its cultivation for biotechnological applications. The E. gracilis was collected from Nasir Bagh, Lahore, Pakistan (31°57′11.6″N, 74°30′62.9″E). The impact of the three selected media (BBM, BG-11, and Chu #10) on the biomass of the isolated strain was evaluated on day 3, 6, 9, 12, and 15 intervals.The experiment was laid out in a Completely Randomized Design (CRD) with two factors, replicated three times. Statistical analysis was performed using two-way ANOVA to test the significance of treatments and their interaction, and Fisher’s Least Significant Difference (LSD) test at p < 0.01 was applied to compare treatment means. The maximum biomass (2.18 g) was obtained in the BG-11 medium followed by BBM (0.85 g) and Chu #10 media (0.34 g) under a light intensity of 120 µmol m-2 sec-1 and a 16:8 light: dark cycle at 25 ºC. BG-11 medium proved to be the most suitable among these media for the growth of E. gracilis, both in terms of maximum biomass production (2.18 g) and average growth rate (0.084 g/day). This study highlights the superior biomass yield of E. gracilis on BG-11 medium, providing a basis for its optimized large-scale cultivation, and enhancing its potential applications in biotechnology, biofuels, and sustainable nutrition.
Keywords: Euglena gracilis; microalgae cultivation; biomass yield; commercial application; BG-11 medium